Beyond Teacher Burnout: Implementing Circle Time as an Adaptive Strategy for Social-Emotional Growth and Collaborative School Culture - Rochman, Catur; Murniati, Ngurah Ayu Nyoman; Prayito, Muhammad (JURNAL AL-TANZIM, 2026)
Teachers' social and emotional competence (SEC) is a crucial factor in improving the quality of education. However, it still faces challenges such as stress, limited collaboration, and a lack of reflective practice. This study aims to analyse the implementation of Circle Time as a managerial strategy to strengthen teachers' SEC and its implications for organisational culture in madrasas. This study used a qualitative case study design. Data were collected through in-depth interviews, participant observation, and document analysis. Data analysis was conducted using an interactive model, which included collection, reduction, presentation, and conclusion drawing. The results showed that Circle Time was implemented through planning, implementation, and evaluation stages. Needs-based participatory planning increased the program's relevance, while reflective practice during the implementation stage enhanced teachers' self-awareness, emotional regulation, empathy, and professional interaction. Evaluation through observation and self- and peer assessments supported continuous improvement. This study contributes by offering Circle Time as an adaptive strategy to strengthen teachers' SEC and build a collaborative school culture. This study implies that Circle Time can be widely applied to develop teachers' social and emotional competence, encourage reflective practice, and build a collaborative school culture.